Guano exposed: Impact of aerobic conditions on bat fecal microbiota. Issue 11 (27th April 2018) - Fofanov, Viacheslav Y.; Furstenau, Tara N.; Sanchez, Daniel; Hepp, Crystal M.; Cocking, Jill; Sobek, Colin; Pagel, Nicole; Walker, Faith; Chambers, Carol L.
Abstract: Bats and their associated guano microbiota provide important terrestrial and subterranean ecosystem services and serve as a reservoir for a wide range of epizootic and zoonotic diseases. Unfortunately, large‐scale studies of bats and their guano microbiotas are limited by the time and cost of sample collection, which requires specially trained individuals to work at night to capture bats when they are most active. Indirectly surveying bat gut microbiota through guano deposits could be a more cost‐effective alternative, but it must first be established whether the postdefecation exposure to an aerobic environment has a large impact on the guano microbial community. A number of recent studies on mammalian feces have shown that the impact of aerobic exposure is highly species specific; therefore, it is difficult to predict how exposure will affect the bat guano microbiota without empirical data. In our study, we collected fresh guano samples from 24 individuals of 10 bat species that are common throughout the arid environments of the American southwest and subjected the samples to 0, 1, and 12 hr of exposure. The biodiversity decreased rapidly after the shift from an anaerobic to an aerobic environment—much faster than previously reported in mammalian species. However, the relative composition of the core guano microbiota remained stable and, using highly sensitive targeted PCR methods, we found that pathogens present in the original, non‐exposed samples could still be recovered after 12 hr of exposure. These results suggest that with careful sample analysis protocols, a more efficient passive collection strategy is feasible; for example, guano could be collected on tarps placed near the roost entrance. Such passive collection methods would greatly reduce the cost of sample collection by allowing more sites or roosts to be surveyed with a fraction of trained personnel, time, and effort investments needed. Abstract : Large‐scale study of bats and their microbiota is limited by the time and cost of fresh sample collection. In this study, we analyze the viability of collecting samples from guano deposits by establishing the effects of postdefecation exposure on the biodiversity and composition of the guano microbiome. We found that the relative composition of the core guano microbiota remained stable after 12 hr of exposure, suggesting that the more efficient, cost‐effective passive collection strategies are feasible in some cases.